Bakteri Asam Laktat dari Buah Mangga Arum Manis (Mangifera Indica L. Var. Arum Manis) - Nur Arfa Yanti; Ardiansyah; Kurnia Yati (Jurusan Biologi Universitas Negeri Makassar, 2022)
Lactic acid bacteria (LAB) are bacteria that are widely used in the food sector because they are safe for consumption. The aim of this study was to obtain lactic acid bacteria from the Arum sweet mango (Mangifera indica L. var. Arum sweet). Isolation of LAB was carried out by pour plate method using specific media de Man Rogosa Sharpe Agar (MRSA) + CaCO3. Characterization carried out included colony morphology, cell morphology, catalase test, and motility test. There were five isolates of lactic acid bacteria that were isolated from the mango fruit, namely BAL1.3, BAL2.1, BAL3.2, BAL4.2 and BAL5.2. The five LAB isolates had the same characteristics as the key LAB characters, namely bacillus (stem) cell shape, Gram positive, non-motile, no endospores and catalase negative. The five LAB isolates were indicated as members of the genus Lactobacilllus.